Anesthesia with topical lidocaine hydrochloride gauzes in acute traumatic wounds in triage, a pilot study. (September 2016) - Ridderikhof, Milan L.; Leenders, Noukje; Goddijn, Helma; Schep, Niels W.; Lirk, Philipp; Goslings, J. Carel; Hollmann, Markus W.
Highlights: Topical lidocaine is effective in combination with vasoconstrictive additives. Utilizing lidocaine hydrochloride-gauzes without these additives in triage is studied. When wounds need sutures, these gauzes don't provide adequate anesthesia. Abstract: Background: Topical application of lidocaine in wounds has been studied in combination with vasoconstrictive additives, but the effect without these additives is unknown. The objective was to examine use of lidocaine-soaked gauzes without vasoconstrictive agents, in traumatic wounds in adult patients, applied in triage. Methods: A prospective pilot study was performed during 6 weeks in the Emergency Department of a level 1 trauma center. Wounds of consecutive adult patients were treated with a nursing protocol, consisting of lidocaine hydrochloride administration directly into the wound and leaving a lidocaine-soaked gauze, until wound treatment. Primary outcome was need for infiltration anesthesia. Secondary outcomes were Numerical Rating Scale (NRS) pain scores, adverse events and patient and physician satisfaction. Results: Forty patients with a traumatic wound were included, 85% male with a wound on the arm. Thirty-seven patients needed a painful procedure as wound treatment. When suturing was necessary, 77% required additional infiltration anesthesia. Mean NRS pain scores decreased from 3.3 to 2.2 after application of the lidocaine gauze. No adverse events were recorded. Of the patients, 60% were satisfied with use of the lidocaine gauzes, compared to 40% of physicians. Conclusion: Lidocaine hydrochloride (2%) gauzes without vasoconstrictive additives cannot replace infiltration anesthesia in traumatic wounds.